MOTIVASI BELAJAR IPS SISWA PADA MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Elpri Darta Putra; Sapriya; Eva Astuti Mulyani; Mitha Dwi Anggriani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the students' social science learning motivation through the Contextual Teaching and Learning (CTL) model for elementary school students of 023 Pulau Kijang. The research design used was quasi-experimental research. The research was conducted on the fifth-grade students of SD 023 Pulau Kijang, in the academic year of 2010/2020 with a number of 45 students. This classroom action research was conducted through four stages, planning, implementation, observation, and reflection. This research consisted of 2 cycles, the first and second cycle. Each cycle consisted of action planning, action implementation, observation, and reflection to be continued to the next cycle. Whilst the data analysis technique used was quantitative statistical analysis to analyze data regarding teachers’ and students’ activities that would be observed. The results indicated that by applying the CTL model, it could provide students with social science learning motivation based on the process and students’ learning outcomes in social science learning subjects for class IV. It was clear that the social science learning process before the implementation of the CTL model has an average percentage level of 70.29 Meanwhile, after the implementation of the CTL model for class V, there was a significant average percentage of 85,59. It showed that the CTL learning model provided better motivation for the students in the learning process.